A BIBLIOGRAPHY ON WINTER CONSTRUCTION, 1940-1967. - Fulwider,Charles W.; Stearman,Jay H. (1968)
The bibliography was derived primarily from a search of the U.S. Army Cold Regions Research and Engineering Laboratory library, the Arctic Bibliography, the Bibliography on Snow, Ice and Permafrost (USA CRREL Report No. 12, Volumes 1-20), the Polar Bibliography, the Industrial Arts Index and the Applied Science and Technology Index. The period covered by the bibliography purposely was limited to the years after 1940 because of the rapid technological advances since World War II. The 751 references are subdivided into twenty-two categories. (Author) Supersedes report dated Jun 65.